An examination of the theory of crimes in common partly establishment standard of joint crime under the factual crime system. (June 2016) - You, Chengjing
Abstract: The established standard of joint crime constitutes the essential issue of joint crime and, in turn, reflects the complexity of joint crime. Studying the established standard of joint crime is not only valuable in terms of the development of legal theories, but is also of considerable importance in guiding best judicial practice. At present, it has caused a heated debate between the theory of crimes in common partly and the theory of objective behavior in common. Under the present system of understanding facts relating to a criminal case, efforts should be made to make a factual judgment about the constitution of a crime, attempt to unify the factual standards determining different types of joint crime, and retain a systematic approach to the science of criminal law on the theoretical basis of "the theory of crimes in common partly." These efforts should then eventually unify the standards relating to joint crime and overcome the difficulty of the "Chapter of Despair".